Microbiology of active chronic otitis media: in comparison with abroad studies - Jaafar, Anwar. S.; AL-Obaidy, Raad Aboud; Dawood, Wisam . S. (AL-Kindy College Medical Journal, 2014)
Background: Chronic otitis media (COM) of mucosal or squamous type is a common problem in otolaryngology practice, the active form of COM is characterized by discharge of pus and is treated by antibiotics to start with, the appropriate antibiotic should be prescribed to avoid antibiotic abuse and guarantee good outcome. Objectives:The objective of this study is to identify the causative organisms of active chronic active otitis media both (mucosal, squamous) type and test their sensitivity to various anti- microbial agents &compare with abroad studies.Methods:A prospective study was done on eighty patients, different ages and sexes were taken and carful history and examination was done, examination under microscope was done with carful suction to ensure absence of cholesteatoma, ear swabs were collected from middle ear discharge, bacteria identified by gram-staining and biochemical tests and antibiotic sensitivity were tested by using disc-perfusion method.Results:The culture results of eighty patients with chronic active otitis media, showed Pseudomonas aeroginosa from 26 patients (32.5%) and Proteus species from 18 patients (22.5%) and Staphylococcus aureus from 12 patients (15%), Providentia from 8 patients (10%) and Sarretia from 6 patients. (7.5%), mixed gram–ve bacteria isolated from 7.5% of patients, Klebsiella Ozaenae from 5%. of patients. no anaerobic bacteria were isolated in this study (table 1, 2).Antibiotic susceptibility showed sensitivity of Ps. Aeroginosa to menepem, third generation cephalosporin, ciprofluxacillin and resistance to gentamicin. Klebsiella Ozaenae showed resistant to many antibiotic also Serratia as shown in table 3. Conclusions:the microbial study of middle ear discharge is very important because the medical treatment is still a main part in treatment of chronic active otitis media so identifying the type of microorganisms and its sensitivity to antibiotics is give a good chance to successful control of the infection